Aligning Governance, Data, and Controls: A Practical Blueprint for Bank Remediation Initiatives (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper presents a structured approach to helping G-SIBs, which have been the subject of multiple compliance orders from both the FRB and OCC since 2010, remediate their compliance problems. This will be accomplished under the direction of a dedicated Remediation Program Manager and the establishment of an 11-pillar framework that contains elements from the FRB SR08-08 policy statements to support a comprehensive approach to sustainability within the areas of risk management, data quality, and compliance oversight, along with enhanced governance and cross-functional collaboration. The methods employed to develop an effective program to remediate regulatory compliance issues included the use of a risk-based triage approach to the prioritization of compliance issues, advanced data analytics to conduct root cause analysis on unresolved issues, and the implementation of a hybrid execution model that employed both Agile and Waterfall methodologies, which resulted in the significant reduction of issues associated with high-risk areas of exposure and improved closure rates. By 2018, the banks had remediated all outstanding regulatory orders from both the FRB and OCC preventing the imposition of substantial fines and ensuring compliance with all regulatory requirements. The overall data architecture that was proposed for reporting compliance remediation results is comprised of a core repository of data and analytical dashboards to monitor compliance status. Future enhancements to the central repository and dashboards will be developed using a cloud-native RegTech and AI/ML-based solution to provide a more proactive solution for addressing complex regulatory compliance issues in the ever-evolving environment of public policy.